2020
DOI: 10.1590/1807-3107bor-2020.vol34.0037
|View full text |Cite
|
Sign up to set email alerts
|

Degree of family cohesion and social class are associated with the number of cavitated dental caries in adolescents

Abstract: Laio da Costa DUTRA (a) Érick Tássio Barbosa NEVES (a) Larissa Chaves Morais de LIMA (a) Monalisa Cesarino GOMES (a) Franklin Delano Soares FORTE (b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
2
9
0
4
Order By: Relevance
“…31 These predictors are more commonly observed when parents, especially mothers, are less educated, 31 as commonly found in vulnerable populations. Adolescents from lower socioeconomic status families, as from disengaged, separated or connected families are more likely to have larger number of cavitated lesions, 33 supporting our study's findings.…”
Section: Discussionsupporting
confidence: 90%
“…31 These predictors are more commonly observed when parents, especially mothers, are less educated, 31 as commonly found in vulnerable populations. Adolescents from lower socioeconomic status families, as from disengaged, separated or connected families are more likely to have larger number of cavitated lesions, 33 supporting our study's findings.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study conducted in Brazil showed that adolescents aged 12 who had high family cohesion went to dental visits more frequently [ 21 ]. Furthermore, other studies of adolescents revealed that a low level of family cohesion was associated with untreated dental caries [ 16 , 24 ]. Therefore, adolescents from families less connected may present worse oral health behaviors [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that higher levels of family cohesion can positively contribute to adequate health behaviors in adolescence [ 22 ], with low levels of family cohesion contributing to lower life satisfaction in adolescents [ 23 ], probably reducing motivation and interest in issues related to oral health. A growing number of cross-sectional studies have examined the association between low family cohesion and dental problems such as dental caries in adolescents [ 16 , 24 ] but the role of family cohesion in adolescents' self-perceived need for dental treatment has not been explored. This information is important because adolescents are influenced by the family environment to make decisions, as well as establish financial, psychological, and emotional dependence with guardians and parents [ 20 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A adolescência é o período em que as condições bucais mais prevalentes ainda dependem da presença de um biofilme patogênico (Souza & Roncalli, 2007;Dutra, 2020). Essa afirmativa está estritamente relacionada a negligência da higiene bucal e a presença de uma dieta rica em carboidratos adotada nessa faixa etária da população (Aguiar et al, 2014;Vazquez Fde et al, 2015).…”
Section: Discussionunclassified
“…Os textos foram organizados em uma classificação dos eixos temáticos abordados pelos estudos nos adolescentes brasileiros. 50% (n=11) dos artigos destacavam necessidade de acesso aos serviços de saúde bucal (da Fonseca et al, 2017;Dutra et al, 2019;Dutra, 2020;Ely et al, 2016;Emerich et al, 2015;Fontanini et al, 2015;Pilecco et al, 2020;Silveira et al, 2015;Vazquez Fde et al, 2015;Veiga da Silva Siqueira et al, 2019); 36% (n= 8) evidenciaram a prevalência e necessidades de cuidados com a saúde bucal (Aguiar et al, 2014;Assaf et al, 2014;Bendo et al, 2012;Cunha & Pereira, 2019;Mail et al, 2015;Massoni et al, 2020;Mauricio Hde & Moreira Rda, 2014) e 17% (n=4) dos estudos selecionados destacaram os conhecimentos e atitudes dos adolescentes em relação as condições de saúde bucal (Dutra et al, 2019;Fonseca et al, 2014;Garcia et al, 2010;Marín et al, 2016).…”
Section: -15 Não Informou O Sexounclassified